Antoni Kępiński’s Philosophy of Medicine – an alternative reading - Zawiła-Niedźwiecki, Jakub (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2016)
Antoni Kępiński remains an often read and quoted author even 40 years after his premature death. Usually he is read in the context of his times and his connections with contemporary philosophy. This paper aims to show other aspects of his reflections on psychiatry. His views on the position of psychiatry within medicine, its methods, psychophysical problems, and other issues are compared with current knowledge and current thought paradigms. The goal is to show that while Kępiński was obviously functioning within a different scientific and philosophical paradigm many of his ideas and reflections can still be found within current debates. The important conclusion is to not hold on to the views that Kępiński held himself because he did not know as much as we do, but to see the importance of the debates that he foresaw even then and possibly learn something from his extensive clinical experience.